Old Karelian personal names - Kuzmin, Denis (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2022)
The article analyzes old personal names of the Karelian population. As the author demonstrates, the revealed corpus of historical Karelian names is yet very incomplete and severely understudied. This is to be due to a number of causes, including the relative scarcity of names recorded in historical documents, the limited number of sources, and the lack of research devoted to medieval Karelian names. Thus, this article is the author’s look into the evolution of the old given names of Karelians and a step towards their further description and study. Kokkuvõte. Denis Kuzmin: Vanad karjalaste isikunimed. Artiklis analüüsitakse Karjala elanikkonna vanu isikunimesid. Nagu autor näitab, on teadaolevate ajalooliste karjalaste nimede korpus veel väga puudulik ja väheuuritud. Põhjusi selleks on mitu, sealhulgas ajalooürikutes kirja pandud nimede suhteline nappus, allikate piiratus, keskaegsete karjala nimede vähene uuritus. Käesolev artikkel annab ülevaate karjalaste vanade eesnimede kujunemisest ning on samm nende edasise kirjeldamise ja uurimise suunas.